Why all Muslims should know the Islamic worldview - Omer, Spahic (islamicity.org, 2018)
A worldview is a comprehensive view of the world we live in and interact with. The view is not physical, but philosophical. It encompasses all animate and inanimate, physical and metaphysical realities. A worldview, furthermore, is about seeking, comprehending, embracing and living the truth. The world exists because of, and for, the truth. The truth, therefore, is embodied and manifested in the world, as much in the simplest and smallest as in the grandest and most sophisticated. A person’s worldview represents his most fundamental beliefs and assumptions about the universe he inhabits. It reflects how he would answer all the “big questions” of human existence: fundamental questions about who and what we are, where we came from, why we’re here, where we’re headed, the meaning and purpose of life, the nature of the afterlife, and what counts as a good life here and now (James Anderson). As the existential centre of gravity, man more than any other being personifies, demonstrates and, at the same time, hankers for the truth. Hence, a worldview - both as an intellectual inquiry and a pursuit of spiritual certitude - signifies a circumcentre of an ontological triangle, so to speak, whose intersection is formed by the perpendicular bisectors originating from three vertices that represent the world, man and the truth.